Women's farming groups in a semi-arid region of Kenya: a case study of Tharaka division, Meru district - Brown, Katrina (1990)
The thesis examines how far women's farming groups are able to foster self-reliance among peasant farmers in Tharaka Division, a semi-arid region of Kenya. This is a particularly impoverished, drought prone part of the country where population pressure is resulting in intensified land use. In the past development policies have increased the vulnerability of peasant farmers making local people increasingly dependent on cash cropping and off-farm sources of income. Many households are headed by women, and the majority of farms are managed by women.